Post-Conflict Reconstruction: Reimagining Khan Younis City Center, Gaza Strip - Shweiki, Husam; Gheidari, Yasaman; Guler, Amine (Palestine Polytechnic University, 2025)
The prolonged conflict in Gaza has inflicted severe and widespread damage on Khan Younis city, resulting in extensive destruction of urban infrastructure, public spaces, and civilian buildings, with an estimated 80% of structures either damaged or rendered uninhabitable. As the scale of devastation necessitates a comprehensive and coordinated effort to reconstruct the city's physical and social fabric, this study conducted comprehensive analyses to understand public spaces in Khan Younis, focusing on the central plaza. It evaluates the geographical and demographic context, assesses the recent conflict's impact, and offers sustainable solutions for recovery and reconstruction. The study identifies public spaces from all neighborhoods on an urban scale. These public plazas will be connected by green corridors to form the green structure of the city. Architecturally, the project proposes to design the city center plaza as a green urban garden that reflects its historical context. The historic Barquq Castle will be restored and pedestrian use will be increased. Memorial walls will be created through participatory design to allow people to remember their lost loved ones. A market area will support women's presence in public spaces, helping them to gain economic independence and feel safe. Safe shelters will be integrated into the basement of the square to provide refuge during conflict, designed to meet international safety standards. The methodologies and recommendations aim to create a scalable model for urban reconstruction applicable to other conflict-affected areas. The destruction in Khan Younis offers a chance to address pre-conflict urban issues. Reconstruction should begin promptly with local and international cooperation, addressing various academic and practical aspects.
Number of pages: 7, 2025 Engineering for Palestine Conference (ENG4PAL) PPU, Hebron, Palestine, September 29-30, 2025
Keywords: Post-Conflict Reconstruction, Humanitarian Crisis, Khan Younis City Centre, Public Space Reconstruction Methodology, Urban Green Corridors, Nature-Based Solutions, Memorial Walls, Women's Economic Empowerment, Safe Shelters